Penerapan Metode Naïve Bayes Pada Klasifikasi Gambar Digital Tumbuhan Obat Sirih Hijau dan Sirih Merah - Prabowo, Rizky; Ariany, Windy Desty; Hermanto, Bambang (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2024)
Plants possess numerous benefits as living organisms. For example, medicinal plants can be distinguished based on factors like their color, texture, and leaf structure. Categorization involves sorting similar plants together while noting their differences. Different techniques, such as the naive Bayes method, can be utilized for this purpose. This study evaluates the efficacy of naive Bayes classification in contrast to the Decision Tree approach. The dataset consists of original data extracted from 2000 images, which are divided into two groups: green betel and red betel. To facilitate comparison, the dataset is split into training and testing sets, with varying ratios ranging from 60:40 to 80:20.